2002
DOI: 10.1002/1522-2683(200208)23:15<2445::aid-elps2445>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an ultraviolet light-emitting diode-induced fluorescence detector in capillary electrophoresis

Abstract: The performance of a fluorescence detector in capillary electrophoresis (CE) using a light-emitting diode (LED) as excitation source is reported. An ultraviolet LED pulsed at a repetition rate of 500 Hz, combined with a time-discrimination and averaging acquisition system, was used. Limits of detection of 3 and 18 fmoles (at a signal-to-noise ratio equal to 3) were achieved for fluorescamine-derivatized bradykinin and lysine, respectively. This system exhibited a linear response for a concentration range betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…14 Hillebrand et al reported on the application of a pulsed (500 Hz) UV-LED (370 nm; ∆λ = 12 nm) for the detection of fluorescence-derivatized bradykinin and lysine at the femtomole level. 15 Although the UV-LED (375 nm, 2 mW; NSHU550A) is commercially available, the Nichia Corporation (http://www.nichia.co.jp) reported on the successful development of high-output ultraviolet LEDs of 380 nm (85 mW; Model, SIRIUS) and 365 nm (100 mW; Model, i-LED), respectively. More recently, Dupuis et al reported on an AlGaN/AlGaN quantumwell UV-LED and a ternary AlGaN UV-LED grown on sapphire, with peak emission wavelengths at 341 nm and 302 nm, respectively, with a narrow line width of ∆λ = 10 nm that can be used at room-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…14 Hillebrand et al reported on the application of a pulsed (500 Hz) UV-LED (370 nm; ∆λ = 12 nm) for the detection of fluorescence-derivatized bradykinin and lysine at the femtomole level. 15 Although the UV-LED (375 nm, 2 mW; NSHU550A) is commercially available, the Nichia Corporation (http://www.nichia.co.jp) reported on the successful development of high-output ultraviolet LEDs of 380 nm (85 mW; Model, SIRIUS) and 365 nm (100 mW; Model, i-LED), respectively. More recently, Dupuis et al reported on an AlGaN/AlGaN quantumwell UV-LED and a ternary AlGaN UV-LED grown on sapphire, with peak emission wavelengths at 341 nm and 302 nm, respectively, with a narrow line width of ∆λ = 10 nm that can be used at room-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Dasgupta and coworkers [4,8] described the use of LED-FD combined with liquid-core waveguide technique in CE, achieving in 200 amole fluorescein of mass detection limit. Recently, Hillebrand et al [9] reported a LED-FD in CE using a pulsed mode-operating ultraviolet LED. Su and Lin [10] determined riboflavin in urine using a blue LED by CE combined with sample stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LED is commercially available at wavelengths ranging from deep-UV to near-IR regions. LED has been used as alternative light source in fluorescence detections [4][5][6]. Unfortunately, owing to its area source and incoherent characteristic, light emitted by an LED usually has a wide divergence angle.…”
Section: Introductionmentioning
confidence: 99%